2016
DOI: 10.3349/ymj.2016.57.4.950
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pulsatility Index on Infarct Volume in Acute Lacunar Stroke

Abstract: PurposeLacunar stroke, in the context of small vessel disease, is a type of cerebral infarction caused by occlusion of a penetrating artery. Pulsatility index (PI) is an easily measurable parameter in Transcranial Doppler ultrasound (TCD) study. PI reflects distal cerebral vascular resistance and has been interpreted as a surrogate marker of small vessel disease. We hypothesized that an increased PI, a marker of small vessel disease, might be associated with a larger infarct volume in acute lacunar stroke.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…In this study, we found that a higher MCA asymmetry [6,7]. Concerning the relationship between TCD parameters and prognosis, MFV and PI were independent prognostic factors for recurrent vascular events in patients with transient ischemic attack or minor ischemic stroke [4] and also useful to predict short-term functional outcome in stroke patients with recanalization after intravenous thrombolysis [17].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, we found that a higher MCA asymmetry [6,7]. Concerning the relationship between TCD parameters and prognosis, MFV and PI were independent prognostic factors for recurrent vascular events in patients with transient ischemic attack or minor ischemic stroke [4] and also useful to predict short-term functional outcome in stroke patients with recanalization after intravenous thrombolysis [17].…”
Section: Discussionmentioning
confidence: 59%
“…Other researchers have reported that an elevated PI is associated with cerebrospinal fluid pressure, cognitive performance, and infarct volume in patients with lacunar infarcts [5][6][7]. However, there is relatively little information on the laterality of each parameter, which includes the association between the lateral difference and some disorders such as cluster headache and acute intracerebral hemorrhage [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This appears to indicate that small atheromatous plaques of the MCA major trunk cause slight stenosis in the larger size group. Kim et al [6] reported that there was a significant positive association between the PI measured by transcranial Doppler (TCD) and infarct volume in acute lacunar stroke. In the present study, infarction size was not significantly associated with PI, but it was associated with PSV of M1.…”
Section: Resultsmentioning
confidence: 99%
“…Neurological deterioration and worse prognosis have been reported and are considered to be Terasawa related to enlargement of infarct volume [5]. Some factors such as the serum cholesterol level [5] and the pulsatility index (PI) of the middle cerebral artery (MCA) [6] are reported to be associated with increased infarct size. However, there are no strong factors that are commonly recognized to be associated with larger size of infarct.…”
Section: Introductionmentioning
confidence: 99%
“…Many TCD-based studies in stroke patients have been conducted using MV and PI. Increased MV was closely related to severe stenosis of relevant intracranial cerebral arteries, and increased PI was associated with small artery disease in diabetes patients and a larger infarction in lacunar stroke [6, 16, 17]. In addition, PI could play a role in estimating intracranial pressure [18].…”
Section: Discussionmentioning
confidence: 99%